Pengaruh Pemberian Rodentisida Erkatril Dalam Pengendalian Hama Tikus (Rattus tiomanicus) Pada Kelapa Sawit (Elaeis guineensis JACQ.) Di PTPN IV Regional 1 Kebun Rantauprapat - Loudgren Three Sitorus; Badrul Ainy Dalimunthe; Yusmaidar Sepriani; Ika Ayu Putri Septyani (Jurnal Penelitian Pertanian Terapan, 2026)
Oil palm (Elaeis guineensis Jacq.) is one of Indonesia's strategic plantation commodities that contributes significantly to the national economy, especially in North Sumatra. The high productivity of oil palm plants is greatly influenced by cultivation management and pest control factors. One of the main pests that often causes significant losses in oil palm plantations is rats, which attack fresh fruit bunches (FFB) and have the potential to reduce both the quantity and quality of the harvest. Therefore, an effective, efficient, and sustainable rat pest control strategy is needed. This study aims to determine the effectiveness of using the rodenticide Erkatril in suppressing the rat population and reducing the level of attacks on oil palm fruit, so that it can be used as a basis for consideration in rat pest management in oil palm plantations. The study was conducted using a completely randomized design (CRD) consisting of three treatments of Erkatril rodenticide application frequency and five replicates. The parameters observed included rat population, percentage of fruit damage, rat mortality rate, and fresh fruit bunch productivity. The observation data were analyzed using Analysis of Variance (ANOVA) to determine the effect of treatment on the parameters observed. If the analysis results showed significant differences, the testing was continued with the Least Significant Difference (LSD) test at a 5% confidence level. The results showed that the frequency of Erkatril rodenticide application had a very significant effect on reducing the rat population, fruit attack rate, rat mortality, and oil palm fresh fruit bunch productivity. Treatment E3, which involved three applications of rodenticide, was the best treatment because it reduced the rat population to the lowest level, significantly reduced the percentage of fruit attacks, increased rat mortality, and produced the highest fresh fruit bunch productivity compared to other treatments. These findings indicate that the use of Erkatril rodenticide with the appropriate application frequency can be an effective rat pest control strategy to increase oil palm productivity.